Analisis Postur Pekerja Bengkel Cutting Fabrikasi Plat Tipis PT. X dengan Metode REBA dan JSI - Ayu, Fifi Kinanti; Sari, Rizqi Novita (Universitas Harapan Medan, 2025)
Ergonomics aims to ensure worker comfort while doing their work. Work posture is very important to determine the effectiveness of a job. Musculoskeletal Disorders (MSDs) are characterized by injuries to muscles, tendons, ligaments, nerves, cartilage, bones, blood vessels in the hands, feet, neck, and back. This study aims to analyze work posture in order to reduce the risk of work accidents. The REBA method analyzes work postures that focus on the body parts of the neck, back, arms, wrists, and feet of workers, and considers external loads and work activities. While the JSI method focuses on effort intensity, effort duration, number of efforts per minute, hand/wrist position, work speed, duration of activity per day. With the analysis of work postures on both workers using REBA, the final score for worker 1 was 10 and for worker 2 was 8, which means that checks and changes in implementation in the work environment are needed. Then, in the analysis of the worker's body posture using the JSI method on worker 1, the JSI value was 5 and on worker 2, the JSI value was 6.75, which means that this type of work is at risk of injury so that changes in the implementation of the work environment are needed. Based on the results of the analysis of work posture using both methods, in the thin plate cutting process, it is necessary to improve facilities and the work environment.